2018
DOI: 10.1016/j.jfma.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Management of dental extractions in patients on warfarin and antiplatelet therapy

Abstract: The study indicated that there is no need to interrupt warfarin (INR<4.0) and antiplatelet therapy before dental extractions in Taiwanese patients. A sufficient hemostasis could be obtained using local measures. This approach can save these individuals from becoming exposed to the risk of thromboembolism and the inconvenience of bridging anticoagulation with heparin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
1
42
0
6
Order By: Relevance
“…In total, 377 articles were identified via the electronic database search and one article in the hand search. After removing duplicates and screening by title and abstract, 18 papers were included for full-text assessment [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Two of these were excluded 27,28 and 16 were included for quantitative and qualitative synthesis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…In total, 377 articles were identified via the electronic database search and one article in the hand search. After removing duplicates and screening by title and abstract, 18 papers were included for full-text assessment [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Two of these were excluded 27,28 and 16 were included for quantitative and qualitative synthesis [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…However, other studies have not found these differences to be statistically significant (18)(19)(20). The percentages of patients suffering post-operative bleeding events was relatively low at between 4.2 and 8.3% for dual antiplatelet therapy compared to control groups (18,20,21). The most important aspect of these studies clinically is that all of the bleeding events were minor and controlled by local measures (16,(18)(19)(20)(21).…”
Section: Clinical Decision-making Based On Key Points From Published mentioning
confidence: 93%
“…The percentages of patients suffering post-operative bleeding events was relatively low at between 4.2 and 8.3% for dual antiplatelet therapy compared to control groups (18,20,21). The most important aspect of these studies clinically is that all of the bleeding events were minor and controlled by local measures (16,(18)(19)(20)(21). The authors drew the conclusion that dual antiplatelet therapy should not be interrupted for dental extractions (16,(18)(19)(20)(21).…”
Section: Clinical Decision-making Based On Key Points From Published mentioning
confidence: 99%
See 1 more Smart Citation
“…The concern around uncontrollable haemorrhage is partly supported by meta-analyses of extractions in patients on dual antiplatelet therapy that found that, rather unsurprisingly, these patients are at an increased risk of bleeding compared to patients who are not taking antiplatelet medications (16,17). However, other studies have not found these differences to be statistically significant (18)(19)(20). The percentages of patients suffering post-operative bleeding events was relatively low at between 4.2 and 8.3% for dual antiplatelet therapy compared to control groups (18,20,21).…”
Section: Clinical Decision-making Based On Key Points From Published mentioning
confidence: 99%